Retention of Information from a Mixed Reality Training on Safety Measures Within an Automotive Plant. - Musule Alfaro, Ahmed; Esparza Mendoza, Javier; Neira-Tovar, Leticia (Revista Daena: International Journal of Good Conscience)
This paper inspect the retention capability of subjects that were exposed to a mixed reality training through a security application Integrated on a Metaquest Device, the application was developed from scratch and we show the pursued steps to carry it out, after the users finished the training, we release an evaluation of the topics seen in the mixed reality training, enhancing that only those who had never received training in industrial safety before would be considered, after 1 month the same evaluation was applied again, to obtain both grades, and with this grades, the percentage of knowledge retention was evaluated, in order to compare it with a traditional class. Also, the schedule is presented based on the development of the application and the tests to be performed.